2021
DOI: 10.3389/fcimb.2021.739874
|View full text |Cite
|
Sign up to set email alerts
|

S100B Inhibition Attenuates Intestinal Damage and Diarrhea Severity During Clostridioides difficile Infection by Modulating Inflammatory Response

Abstract: The involvement of the enteric nervous system, which is a source of S100B, in Clostridioides difficile (C. difficile) infection (CDI) is poorly understood although intestinal motility dysfunctions are known to occur following infection. Here, we investigated the role of S100B in CDI and examined the S100B signaling pathways activated in C. difficile toxin A (TcdA)- and B (TcdB)-induced enteric glial cell (EGC) inflammatory response. The expression of S100B was measured in colon tissues and fecal samples of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 74 publications
0
29
0
Order By: Relevance
“…S100B was found to regulate cytokine synthesis. Mice treated with pentamidine also showed lower colonic concentrations of proinflammatory cytokines, including IL-6, IL-8, IL-1β, IL-23, and GM-CS, but not IL-33 and IL-22 levels were even found to be higher compared to untreated mice (Costa et al, 2021). More specifically, the addition of TcdA and TcdB to a rat EGC cell line (EGC PK060399) showed that stimulation with C. difficile toxins increased both S100B release and IL-6 expression by these cells (Costa et al, 2021).…”
Section: Clostridioides Difficile Producing Toxin a And Toxin Bmentioning
confidence: 88%
See 2 more Smart Citations
“…S100B was found to regulate cytokine synthesis. Mice treated with pentamidine also showed lower colonic concentrations of proinflammatory cytokines, including IL-6, IL-8, IL-1β, IL-23, and GM-CS, but not IL-33 and IL-22 levels were even found to be higher compared to untreated mice (Costa et al, 2021). More specifically, the addition of TcdA and TcdB to a rat EGC cell line (EGC PK060399) showed that stimulation with C. difficile toxins increased both S100B release and IL-6 expression by these cells (Costa et al, 2021).…”
Section: Clostridioides Difficile Producing Toxin a And Toxin Bmentioning
confidence: 88%
“…inflammation [reduced histological colonic damage and reduced tumor necrosis factor α (TNF-α) levels, among others] (Hing et al, 2013). Beneath the intestinal epithelial layer lie enteric glial cells (EGCs) that release a number of mediators, such as interleukins, NO, and S100 calcium-binding protein (S100B) and seem to be involved in the immune responses to C. difficile (Cirillo et al, 2011;Macchioni et al, 2017;Costa et al, 2021). In colonic biopsies from both CDI patients and CDI mice increased S100B was observed compared to control subjects and uninfected mice respectively (Costa et al, 2021).…”
Section: Clostridioides Difficile Producing Toxin a And Toxin Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory response is a very complex biological process, which has an important role in many diseases ( Costa et al., 2021 ; Li et al., 2021 ; Lu et al., 2021 ; Wang J. et al., 2021 ). Previous studies showed that inflammatory response played a critical role in the onset of depression, and the disturbance of inflammation levels could increase the incidence of depression ( Leonard, 2018 ; Colasanto et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…High concentration (µM) of S100B is proin ammatory. In a pathological condition, reactive EGCs can trigger, support and amplify gut in ammation via S100B protein [5][6][7][8] . Many studies have supported S100B may induce gut ora dysbiosis 7,9 , epithelial barrier disruption 5,9 and blood-brain barrier (BBB) impairment 10,11 .…”
Section: Introductionmentioning
confidence: 99%